(3GdOdjd dOQGSGJ GdLOhi GdGbJUGOjI (B/s - (3CMeO, BOe egOjs ((3GdbGgQI(B: s (3GdTQcI GdYGdejI ddWHGYI hGdfTQ(B, s, 1999)
(3OQGSI GdLOhi GdGbJUGOjI(B- (3eQGMd GYOGO OQGSI GdLOhi(B- (3GdOQGSI GdJShjbjI(B- (3GdOQGSI GdafjI (B- (3WQb Jbjje GdeTQhYGJs
(3GdedGMb h GdeQGLYs
Keywords: (3GdJNWjW GdEbJUGOjs; (3OQGSI GdLOhis; (3OQGSI GdLOhi(B- (3GdeTQhYGJs